DEVELOPMENT OF ELECTRONIC MODULE BASED ON 3D PAGEFLIP PROFESSIONAL IN SUBJECT EQUIPMENT MACHINE PICTURES - Nopriyanti, Nopriyanti; Kurniawan, Elfahmi Dwi; Dewi, Safira Permata (Sriwijaya University Learning and Education International Conference, 2018)
This research is a development research consisting of two development models, namely: (1) Multimedia product development model according to William. W. Lee & Diana Owens and (2) Evaluate the development using Rowntree. The development of this electronic module was adopted from the development steps of Owens & Lee which have five stages as follows: (1) analysis consisting of field studies & needs analysis in the basic competency learning process for installing electricity lighting and wiring systems; (2) product design consists of: determining media specifications, creating a flowchart, determining learning strategies, determining the software to be used; (3) product development; (4) implementation; and (5) evaluation. The results of this research are from the assessment of media experts and material experts about the feasibility of this electronic module, in terms of the display aspects of 31 average 4.43 with very good criteria. Programming aspects amounted to 32 with an average of 4.57 criteria Very Good, learning aspects amounted to 37 average 4.63 with very good criteria, and material aspects amounting to 50 average 4.55 with the criteria Very Good. While the results of the assessment of students field tests on aspects of the display, on the aspects of programming, on aspects of learning, and on the aspect of content has an assessment of 847 on average 4,405 with the criteria of "very good".